2008
DOI: 10.1128/aac.01538-07
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-Resistant Pathogens in Intensive Care Units in Canada: Results of the Canadian National Intensive Care Unit (CAN-ICU) Study, 2005-2006

Abstract: , 19 medical centers collected 4,180 isolates recovered from clinical specimens from patients in intensive care units (ICUs) in Canada. The 4,180 isolates were collected from 2,292 respiratory specimens (54.8%), 738 blood specimens (17.7%), 581 wound/tissue specimens (13.9%), and 569 urinary specimens (13.6%). The 10 most common organisms isolated from 79.5% of all clinical specimens were methicillin-susceptible Staphylococcus aureus (MSSA) (16.4%), Escherichia coli (12.8%), Pseudomonas aeruginosa (10.0%), Hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
157
3
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(216 citation statements)
references
References 32 publications
(37 reference statements)
39
157
3
16
Order By: Relevance
“…Other studies reported similar resistance rates of P. aeruginosa [24,25]. In contrast to our results, the resistance rates of A. baumannii and P. aeruginosa are low in many developed countries [2,17]. P. aeruginosa and A. baumannii isolated from centers in the United States in the MYSTIC program (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) were characterized by higher susceptibilities to meropenem 85.4% and 45.7%, respectively [28].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Other studies reported similar resistance rates of P. aeruginosa [24,25]. In contrast to our results, the resistance rates of A. baumannii and P. aeruginosa are low in many developed countries [2,17]. P. aeruginosa and A. baumannii isolated from centers in the United States in the MYSTIC program (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) were characterized by higher susceptibilities to meropenem 85.4% and 45.7%, respectively [28].…”
Section: Discussioncontrasting
confidence: 56%
“…The spectrum of pathogens in ICUs may change from country to country with time and by hospital, type of ICU, and specific patient population [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Tobramycin, kanamycin-A and neomycin-B were purchased from Sigma Aldrich Canada Ltd (Oakville, Ontario, Canada). 10 …”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…10 Stock solutions of amphiphilic aminoglycosides were prepared to a concentration of 512 mg ml À1 in water. Organisms were subcultured and isolated on blood agar, suspended in 3 ml of Mueller-Hinton broth at the turbidity of a 0.5 M McFarland standard, and diluted to approximately 10 5 CFU ml À1 before introduction into tubes containing serially diluted lipopeptide antibiotic in Mueller-Hinton broth.…”
Section: Mic Determinationmentioning
confidence: 99%
“…MRSA bacteremia emergence among ICU patients has been associated with several factors, which can be classified according to three groups: a) those related to the microorganisms, primarily the spread of resistant clones (8); b) those associated with the host, which include age, sex, presence of comorbidities (particularly chronic illnesses), previous use of antibiotics and invasive devices (9)(10)(11)(12), and c) the characteristics of hospital and community environments (9,11,13), particularly previous use of antibiotics given the high risk associated with this factor and the control of crosstransmission of microorganisms.…”
mentioning
confidence: 99%